Kebijakan Pemerintah untuk Meningkatkan Pertumbuhan Ekonomi di Indonesia Pasca Covid-19 - Sholihah, Istiqomatis; Fitriani, Lilis Eka (CV. Civiliza Publishing, 2023)
ntroduction: Covid-19 has hurt the global economy, including in Indonesia. This research analyzes government policies to increase economic growth in Indonesia after Covid-19. Research Methods: The method used is a qualitative method with a literature study approach. The type of data used is secondary. Data collection in this research was through journals, books and websites. Results: The research results show that the government's policy to increase economic growth after Covid-19 is as follows: (1) there is a policy in the health sector in the form of vaccination created by the government. (2) monetary policy in the form of minimizing state expenditure during Covid-19, raising or lowering bank interest rates, and providing cheap credit for the Indonesian people as well. (3) fiscal policy in the form of distribution of cash assistance and necessities, encouraging MSMEs. Of these three policies, the policy that has the most significant influence on economic growth after Covid-19 is the vaccination policy. As a result of this policy, Indonesia's economic growth will increase from 2.97% to 5.72% in 2020 to 2022. Conclusion: From this research, it can be concluded that economic growth has increased after Covid-19 occurred, which was caused by the existence of very effective fiscal and monetary policies to increase economic growth in Indonesia.